Odpowiedź :
a)
[tex]-4x + 13 = x + 3\\\\-4x-x = 3-13\\\\-5x = -10 \ \ /:(-5)\\\\\boxed{x = 2}[/tex]
b)
[tex]0,9y - 1 = 0,5 - 0,6y\\\\0,9y + 0,6y = 0,5+1\\\\1,5y = 1,5 \ \ /:1,5\\\\\boxed{y = 1}[/tex]
c)
[tex]6(a+4) = -3(-2a-5) \ \ /:3\\\\2(a+4) = -(-2a-5)\\\\2a+8 = 2a+5\\\\2a-2a = 5-8\\\\0 = -3, \ sprzecznosc, \ brak \ rozwiazania\\\\0 \neq -3[/tex]
ROZWIĄZANIE
a) -4x + 13 = x + 3
-4x + 13 = x + 3 | - x
-5x + 13 = 3 | - 13
-5x = -10 | : 5
x = 2
b) (zamieniłem y na x, ponieważ się przyzwyczaiłem).
0,9x - 1 = 0,5 - 0,6x | + 1
0,9x = 0,5 - 0,6x + 1 | + 0,6x
0,9x + 0,6x = 0,5 + 1
1,5x = 1,5 | : 1,5
x = 1
c) (zamieniłem a na x, ponieważ się przyzwyczaiłem).
6(x + 4) = -3(-2x - 5)
6x + 24 = 6x - (-15) | - 24
6x = 6x - (-15) - 24 | - 6x
6x - 6x = -15 - 24
0 ≠ -39
MAM NADZIEJĘ, ŻE POMOGŁEM
POZDRAWIAM!
:)
<3